Crime at places of worship: a geospatial analysis - Denney, Andrew S. (Criminal justice studies, 2022)
Many religions often require followers to attend services at physical places of worship (PWs). However, the combination of individuals interacting with one another and the mere presence of physical structures for worship create numerous crime opportunities. The current study examines 6,772 crimes reported to police that occurred at PWs over a two-calendar year period (2009–2010) in one large Southern U.S. metropolitan city. Specifically, this study examines the types/frequencies of crime reported to police at PWs and the geospatial characteristics of PWs that were hotspots. In total, 78 crime categories occurred in the 1,081 unique cases, with theft being the most common offense. Additionally, most hotspot PWs were located near major intersections or bypasses. Policy implications and directions for future research will also be discussed.